265. Optimization of a three-phase computed tomography urography (CTU) protocol with retrospective and prospective study. (December 2018) - Marini, P.; Bona, R.; Pinna, F.; Poggiu, A.; Tamponi, M.; Piras, F.; Profili, S.
Abstract : Purpose: To optimize a three-phase CTU in order to obtain the best trade-off between image quality and radiation dose. Methods and materials: Considering the increase in CT examinations in our hospital, a high dose clinical protocols optimization program was undertaken. A CTU protocol was optimized, with 128-slice Siemens tomography, with CareDose4D for the real-time mA modulation. Starting from a retrospective analysis of a cohort of 43 patients (medium weight 66, 9 kg), in terms of CTDIvol and SSDE (Size Specific Dose Estimates), we obtained a mean total effective dose of 26, 7 mSv (estimated with CTExpo V2.0). Analyzing each protocol phase we realized to have a high margin to reduce dose. Taking as starting point AAPM indications[1] we identified a set of candidate protocols and used them for Catphan 600 Phantom acquisitions, all with automatic dose modulation and different mAs ref options. The quality reference mAs ref represents the effective mAs (mA x rotation time/pitch) value suitable for an average-sized patient weighing 70–80 kg. We analyzed image quality of the scans in terms of noise, spatial resolution and low contrast, and then we chose the protocol to be clinically validated. Finally we made a prospective analysis of 18 patients (medium weight 66, 4 kg), again in terms of CTDIvol, SSDE and effective dose. Results: Among all phantom acquisitions we chose a protocol with a noise decrease of 11% and a minimal loss of contrast (0, 09% on 3 mm detail). The MTF50 value passes from 3, 21 lp/mm to 3, 08 lp/mm. The main radiological parameters of the protocol are summarized in the table below (gray for old protocol, white for the new one). The mean effective dose passed from 25, 7 mSv to 14, 1 mSv. Conclusions: It was possible to reduce the dose by 45% without affecting the image quality.